Cervical cancer prevention in a selected group of nurses on the background of the Multidimensional Health Locus of Control Scale (MHLC) - Malinowska-Lipień, Iwona; Gniadek, Agnieszka; Doros, Joanna; Brzostek, Tomasz; Cisek, Maria; Kawalec, Ewa; Reczek, Agata (Polish Journal of Public Health, 2012)
Introduction. The opportunities to improve prevention and early detection of cervical cancer and improvement of the treatment outcomes are closely related to knowledge, attitudes and women’s behavior. Nurses and midwives due to the specificity of their work have a significant role in the prevention and early detection of female cancers. Aim. Evaluation of prevention cervical cancer in a group of nurses on the background of the Multidimensional Health Locus of Control Scale (MHLC). Material and methods. The study was carried out in September 2008 among 100 randomly selected nurses working in hospitals all around Cracow. The study used the method of diagnostic survey, tools included: a questionnaire and MHLC Scale). Results. One third of the nurses acknowledged that they had annually gynecological checkup, 15% every six months and more often, and as many as 15% of women did not remember the last time they were at the gynecologist. Pap smear was performed every year by 31% of respondents, every two years by 18% of women, and once every three years by 11%. Nearly one third of nurses had a smear test done more than three years ago, and 12% did not remember the last time it was made. The average value of the internal health locus on the scale of MHLC was 25.60, indicating that the respondents were convinced that the control over their own health depends on themselves. Conclusions. Nurses’ health behavior reduced the risk of developing cervical cancer, but did not promote its early detection by avoiding the regular gynecological checkups and Pap tests. Nurses were convinced more often that their own health was in their hands but however, did not show this type of behavior in the preventive actions.